Parameterization of Convection in a Rotating Stratified Ocean: Comparison of Numerical and Laboratory Experiments with Theory - Hufford, Gwyneth E (1995)
Laboratory and numerical experiments are carried out in a parameter regime relevant to open-ocean deep convection. We consider the case of convection in a rotating stratified ocean of finite depth. Convection is induced from the surface by extracting buoyancy over a circular area. The external parameters are buoyancy forcing of strength B,, applied over a circular area of radius R,, the rotation rate is measured by f, ambient stratification N and finite depth H. Theoretical scaling predictions are derived to describe the length and velocity scales of the convective chimney as it adjusts under gravity and rotation, and breaks up through baroclinic instability. The scales of interest include the number (M), size (leddy) and strength (Urim) of the baroclinic eddies formed. Also of interest are the final depth of penetration of the convective mixed layer (dfinal) and the final volume of convectively produced water (Vinal). These scales are tested against the laboratory and numerical experiments and found to be appropriate. We show that for this idealized problem dfinal depends only on the size and strength of the forcing and the ambient stratification encountered by the convection event; it does not depend explicitly on rotation. The volume of convectively modified water produced continues to increase as long as forcing continues, but the rate of production depends again only on the size and strength of the forcing and on the ambient stratification. The implications of the work to deep water formation in the Labrador Sea and elsewhere are discussed. Finally the study has relevance to the role and representation of baroclinic eddies in large-scale circulation of the ocean.